Responsible consumer and lifestyle: Sustainability insights (2020)
Environmental changes resulting from human activity and the negative impact of civilisational megatrends are being noticed and criticised increasingly often, and their consequences are becoming extremely severe. If people do not change their habits, changes in our ecosystems will become irreversible and it will be impossible to live in such environment. Thus, the aim of the paper is to review the lifestyles of responsible consumers against the background of the sustainable development paradigm. To engage in the debate as to how a sustainable lifestyle can be operationalized, we conducted a traditional, narrative literature review. Apart from revising the theoretical framework of a sustainable lifestyle, we describe selected lifestyles (such as LOHAS, wellness, hygge, lagom, slow living, smart living, lowcarbon lifestyles) and consumer behaviour patterns (fair trade, values and lifestyle segmentation). Each of these lifestyles relates to a broader or narrower extent to sustainable development, but none of the lifestyles is universal. Conscious and responsible consumer behaviour requires a long-term process and to a large extent depends on individual, political and marketing factors. Finally, we made an evaluation of the research used, pointing out challenges to be implemented, which will contribute to the development, enhancement and prominence of a sustainable lifestyle.